Attitudes toward criminal Jjstice policies: further evidence against the “gender gap” - Burton, Alexander L. (Gender and crime, 2024)
For decades, scholars have examined the role of gender in shaping attitudes toward criminal justice policy. Specifically, research has attempted to explore whether a “gender gap” in public attitudes exists. Although women tend to differ from men regarding patterns of offending and victimization experiences, tens of studies reveal that women’s attitudes toward crime and justice policies tend to align with men’s. Using national-level data collected by YouGov (n = 1,000), we examine men’s versus women’s attitudes toward two broad sets of policies: criminal record-related policies (e.g., expungement) and the use of specialty courts (e.g., drug courts). This chapter adds additional evidence to the position that a gender gap in attitudes toward crime and justice policy does not exist.